Valuation of three different anaesthetic protocols on complete blood count and biochemical parameters on Wistar rats - LELOVAS, P. P.; STASINOPOULOU, M. S.; BALAFAS, E. G.; NIKITA, M. A.; SISKOS, N. T.; KOSTOMITSOPOULOS, N. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The objective of the current study was to determine the impact of three different anaesthetic protocols on blood and biochemical parameters. Eighteen female Wistar rats (HsdOla:WI) 3 months old, weighting 197.09 ± 7.39 g were used. Baseline blood collection was performed in all animals from the lateral coccygeal vein for evaluation of glucose. The animals were then randomly allocated to receive one of three different anaesthetic protocols: dexmedetomidine/ketamine intramuscularly (0.25 mg/kg and 50 mg/kg respectively), or isoflurane 0.2 ml on cotton inside a syringe case, or isoflurane administered by vaporiser (5% induction and 2-3% maintenance of anaesthesia, delivered in oxygen flow 1 L/min). Blood samples were collected from caudal vena cava for complete blood count and biochemical analysis, while the lung and the liver were harvested for histological evaluation. Comparison between groups, as far as complete blood count parameters is concerned, revealed statistical significant differences in red blood cells, haematocrit and haemoglobin values with lower values being observed in vaporiser anaesthesia group. Furthermore, within group comparison revealed statistical significant differences for glucose in all three groups. No evidence of inflammatory, degenerative neoplastic or toxicity related lesions were observed during histological evaluation of the lung and liver.